Modern gastronomic technologiesin optimization of pro-health food potential - Szponar, Bogdan; Marzec, Agnieszka; Skrzypek, Michał (Polish Journal of Public Health, 2018)
All human senses participate in the sensory evaluation of food, which means that such features as taste, flavour, appearance, or texture determine the acceptance and choice of a dish. Seeking to satisfy consumer requirements and offer a dish or food with the desired organoleptic features, the food industry initially used a wide range of food additives compensating for the loss of colour, taste or flavour of the dish. At present, with an increase in consumers’ awareness and nutrition knowledge, departure is observed from the use of food additives to the benefit of using modern technologies in the food industry. The progress in food science, concerning especially, the phenomena taking place during the storage or processing of food, gives direction to the application of modern technical solutions or materials, and also provides guidelines within the area of gastronomic technology concerning the shaping of not only organoleptic features of the dish, but also activities aiming at the preservation of pro-health potential of food. This issue becomes even more important in the context of increasing epidemics of chronic non-communicable diseases (NCD) in contemporary western societies, in the etiopathogenesis of which, health behaviours play a crucial role. The subject of the report will be analysis of the current state of knowledge in the area of food and nutrition sciences, concerning the possibility of using modern gastronomic technologies in order to preserve or enhance the pro-health potential of food, possible to use within the primary and secondary prevention of NCD.